MASYARAKAT DAN NEGARA MENURUT AL-FARABI - Kurniawan, Puji (IAIN Padangsidimpuan, 2018)
According to Al-Farabi, humans are social creatures who cannot and cannot live alone, for that humans must live in society and help one another. The basic nature of human life in a society and a state encourages people to live socially and help each other for common interests in achieving life goals, namely happiness. Because the best people are people who live in cooperation and help each other to achieve happiness.